Pertumbuhan dan Sebaran Penduduk Perkotaan di Kabupaten Cirebon - Nuri Setiawati; Fadjar Hari Mardiansjah (Jurusan Perencanaan Wilayah dan Kota, 2023)
Sustainable urbanization has led to an overall increase in the world’s population in urban areas. An important spatial characteristic of urbanization is the expansion process of urban regions into their surroundings that transforms peripheral areas into suburban and peri-urban areas. The process is also occurred in Cirebon Regency that is affected by the expansion process of a small- city in Java, that is the City of Cirebon. The urbanization process in the area brings impacts on the widening of urban areas and forming a metropolitan region, formed by the city and the regency. This research aims to analyse urban population growth and their distribution in Cirebon Regency, as part of urbanization process in the region. Using a combination of quantitative and qualitative methods, descriptive statistical analysis, degree of urbanization and spatial analysis, the urbanization and peri-urbanization process were analysed by useing secondary data in the form of village data from all villages in the Cirebon Regency. The So that the peri-urbanization urbanization pattern is formed in Cirebon Regency, which is also characterized by the increasing distribution of population density with the value of population density increasing each period. development of the urban population is influenced by two main factors, internal and external which support the development of rural-urban and urban areas.